Behaviorism Perspective on English as Foreign Language (EFL) Program of an Islamic Boarding School: Theoretical and Application - Siti Rofiati; Annisa Murdiana Putri; Koesoemo Ratih; Endang Fauziati (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
Repetition and reinforcement in structured conditions is normally found in language learning in a boarding school setting. But there is still view discussion on it as investigating this area needs time and complex analysis. As in this study, theoretical and application aspect of behaviorist perspective in the English as Foreign Language (EFL) Program will be investigated in an Islamic boarding school context. Known with the observable behavior, reinforcement system, conditioning process, and language learning structured approach, behaviorism is particularly suitable with highly controlled and structured environment called as a boarding school. This study focuses on the prominence of behavioral concepts such as stimulus-response, reinforcement and repetition in language learning program.  The EFL curriculum in an Islamic Boarding school show that teachers, staffs and students can implement the reinforcement and practice through controlled repetition as a way to increase language proficiency in a structured environment. Some real-life application of behaviorist technique will be explored which highlight on how behaviorist influence students’ engagement, motivation and retention in the language learning. This study found that behaviorism in EFL offers recommendation regarding possible improvements in EFL teaching strategies in boarding schools.